2020
DOI: 10.14336/ad.2020.0604
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Biomarkers in Myocardial Fibrosis

Abstract: Myocardial fibrosis is observed in various cardiovascular diseases and plays a key role in the impairment of cardiac function. Endomyocardial biopsy, as the gold standard for the diagnosis of myocardial fibrosis, has limitations in terms of clinical application. Therefore, biomarkers have been recommended for noninvasive assessment of myocardial fibrosis. This review discusses the role of biomarkers in myocardial fibrosis from the perspective of collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 148 publications
(157 reference statements)
1
29
0
2
Order By: Relevance
“…Through the screening of sequencing results, we found that HKE restored the expression of fibrosis markers Acta1 ( Schwartz et al, 1986 ) and Fn1 ( Knowlton et al, 1992 ), which were verified by qRT-PCR ( Figures 5A,B ). In addition, 12 collagen-coding genes, which are also fibrosis markers ( Ding et al, 2020 ), underwent significant changes after HKE intervention ( Supplementary Figure S6 ). Together, these results provide important insights into the molecular mechanism by which HK alleviates myocardial fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Through the screening of sequencing results, we found that HKE restored the expression of fibrosis markers Acta1 ( Schwartz et al, 1986 ) and Fn1 ( Knowlton et al, 1992 ), which were verified by qRT-PCR ( Figures 5A,B ). In addition, 12 collagen-coding genes, which are also fibrosis markers ( Ding et al, 2020 ), underwent significant changes after HKE intervention ( Supplementary Figure S6 ). Together, these results provide important insights into the molecular mechanism by which HK alleviates myocardial fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrosis is known as the first stage of diabetic cardiomyopathy [ 60 ]. Fibrosis biomarkers, including TGF-β1, TGF-β2, and CTGF as fibrosismarkers, and FSP1, POSTEN, and FN-1 as tissue remodeling markers have been systematically examined [ 61 , 62 ]. We found that the expressions of these genes were all increased in diabetic hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular biomarkers play an essential role in the diagnosis, risk stratification, and treatment of patients with cardiac diseases such as heart failure, dilated cardiomyopathy, and hypertrophic cardiomyopathy [24]. In recent years, much attention has been paid to searching for markers that would allow the noninvasive assessment of the degree of myocardial fibrosis and its possible consequences [20].…”
Section: Markers Of Fibrosismentioning
confidence: 99%
“…Endomyocardial biopsy is the gold standard in the diagnosis of myocardial fibrosis, but it has limitations in terms of clinical application. Biomarkers seem to be safer in diagnosis, treatment monitoring, and prognosis [24]. 4.1.…”
Section: Markers Of Fibrosismentioning
confidence: 99%